2002
DOI: 10.1128/aac.46.8.2327-2332.2002
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Stability Studies of Antipseudomonal β-Lactams for Potential Administration through Portable Elastomeric Pumps (Home Therapy for Cystic Fibrosis Patients) and Motor-Operated Syringes (Intensive Care Units)

Abstract: The stability of antipseudomonal ␤-lactams in concentrated solutions was examined in view of their potential administration by continuous infusion with external pumps (for intensive care patients) or with portable pumps carried under clothing (for cystic fibrosis patients). Aztreonam (100 g/liter), piperacillin (128 g/liter, with tazobactam), and azlocillin (128 g/liter) remained 90% stable for up to more than 24 h at 37°C (mezlocillin [128 g/liter] was stable at 25°C but not at 37°C). Ceftazidime (120 g/liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
123
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(141 citation statements)
references
References 40 publications
11
123
0
2
Order By: Relevance
“…In addition, plasma protein binding is reported to be only 2% (7); therefore, binding to albumin in fetal bovine serum (FBS) supplemented with Dulbecco's modified Eagle medium (DMEM) is not expected to be a significant factor. Meropenem has been reported to be thermally unstable in aqueous solutions (10,12,17); therefore, we determined the stability of meropenem and the other carbapenems at 37°C in water, 7H9 broth medium, and the medium used with the infected macrophages in the susceptibility assay (DMEM) by liquid chromatography (LC)-mass spectrometry (MS) using a Luna NH2 column with a single quadrupole mass-selective detector (Agilent MSD, model G1946DSL). Additional details for this and other experiments can be found in the supplemental material.…”
mentioning
confidence: 99%
“…In addition, plasma protein binding is reported to be only 2% (7); therefore, binding to albumin in fetal bovine serum (FBS) supplemented with Dulbecco's modified Eagle medium (DMEM) is not expected to be a significant factor. Meropenem has been reported to be thermally unstable in aqueous solutions (10,12,17); therefore, we determined the stability of meropenem and the other carbapenems at 37°C in water, 7H9 broth medium, and the medium used with the infected macrophages in the susceptibility assay (DMEM) by liquid chromatography (LC)-mass spectrometry (MS) using a Luna NH2 column with a single quadrupole mass-selective detector (Agilent MSD, model G1946DSL). Additional details for this and other experiments can be found in the supplemental material.…”
mentioning
confidence: 99%
“…(2002) reported that when stored at temperatures of 30 °C and higher, aqueous solutions of cefepime, exhibited a colorimetric change from light yellow to dark red. [10] This colour change was accompanied by a significant increase in the pH of the solution, thus, suggesting the presence of alkaline degradation products. Fubara et.…”
Section: Introductionmentioning
confidence: 99%
“…The instability of cephalosporins in aqueous media is as a result of the highly reactive beta lactam ring, which is susceptible to base catalysed hydrolysis. [10] Degradation studies of cefepime conducted by Sprauten et al (2003) indicated that ring opening of the beta lactam moiety occurred initially, followed by cleavage of the C3 substituent, N-methylpyrrolidine (NMP, II), an acyclic tertiary amine. [4] As NMP is a recognised degradation product, the United States Pharmacopoeia (USP) states that in cefepime for injection the limit of N-methylpyrrolidine 'must not exceed more than 1.0% w/w relative to cefepime [12] and in cefepime hydrochloride 'must not exceed more than 0.3% w/w relative to cefepime.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meropenem and imipenem are not good candidates. On the other hand, some other antibiotics are stable such as piperacillin/tazobactam; ceftazidime and vancomycin (Viaene et al, 2002). So, not only the appropriate dose, usually larger doses than standard regimen are necessary, but also the right mode of administration could help to resolve this clinical situation.…”
Section: Antibiotic Administration Strategiesmentioning
confidence: 99%